THE ROLE OF SPECIFIC ASPECTS OF SOIL CAPILLARITY AND POROSITY IN PRACTICE - Ikromov , Ravshan Ahad o‘g‘li; Azimova, Go‘zal Adizovna (Educational Research in Universal Sciences, 2024)
This scientific article conducts a thorough examination of the specific facets governing soil capillarity and porosity, aiming to provide a detailed understanding of their roles in agricultural systems. Employing a multidisciplinary approach involving field observations, laboratory analyses, and modeling techniques, the study navigates the intricate dynamics of capillarity and porosity properties. The investigation sheds light on the nuanced relationships between soil structure, water movement, and plant interactions, offering valuable insights for the sustainable management of soil resources in agriculture.